Surgical properties and survival of a pericardial window via left minithoracotomy for benign and malignant pericardial tamponade in cancer patients - Celik, Sezai (BioMed Central, 2012)
BACKGROUND: Surgical drainage is a rapid and effective treatment for pericardial tamponade in cancer patients. We aimed to investigate the effectiveness of pericardial window formation via mini-thoracotomy for treating pericardial tamponade in cancer patients, and to evaluate clinical factors affecting long-term survival. METHODS: Records of 53 cancer patients with pericardial tamponade treated by pericardial window formation between 2002 and 2008 were examined. Five patients were excluded due to insufficient data. Kaplan-Meier and Cox regression analysis were used for analysis. RESULTS: Forty-eight patients (64.7% male), with a mean age of 55.20 ± 12.97 years were included. Patients were followed up until the last control visit or death. There was no surgery-related mortality and the 30-day mortality rate was 8.33%; all died during postoperative hospitalization. Morbidity rate was 18.75%. Symptomatic recurrence rate was 2.08%. Cancer type and nature of the pericardial effusion were the major factors determining long-term survival (P <0.001 and P <0.004, respectively). Overall median survival was 10.41 ± 1.79 months. One- and 2-year survival rates were 45 ± 7% and 18 ± 5%, respectively. CONCLUSION: Pericardial window creation via minithoracotomy was proven to be a safe and effective approach in surgical treatment of pericardial tamponade in cancer patients. Cancer type and nature of pericardial effusion were the main factors affecting long-term survival.